Recurrent major depression and right hippocampal volume: A bivariate linkage and association study. Issue 1 (20th October 2015) - Mathias, Samuel R.; Knowles, Emma E. M.; Kent, Jack W.; McKay, D. Reese; Curran, Joanne E.; de Almeida, Marcio A. A.; Dyer, Thomas D.; Göring, Harald H. H.; Olvera, Rene L.; Duggirala, Ravi; Fox, Peter T.; Almasy, Laura; et al.
Abstract: Previous work has shown that the hippocampus is smaller in the brains of individuals suffering from major depressive disorder (MDD) than those of healthy controls. Moreover, right hippocampal volume specifically has been found to predict the probability of subsequent depressive episodes. This study explored the utility of right hippocampal volume as an endophenotype of recurrent MDD (rMDD). We observed a significant genetic correlation between the two traits in a large sample of Mexican American individuals from extended pedigrees ( ρ g = −0.34, p = 0.013). A bivariate linkage scan revealed a significant pleiotropic quantitative trait locus on chromosome 18p11.31‐32 (LOD = 3.61). Bivariate association analysis conducted under the linkage peak revealed a variant (rs574972) within an intron of the gene SMCHD1 meeting the corrected significance level ( χ 2 = 19.0, p = 7.4 × 10 −5 ). Univariate association analyses of each phenotype separately revealed that the same variant was significant for right hippocampal volume alone, and also revealed a suggestively significant variant (rs12455524) within the gene DLGAP1 for rMDD alone. The results implicate right‐hemisphere hippocampal volume as a possible endophenotype of rMDD, and in so doing highlight a potential gene of interest for rMDD risk. Hum Brain Mapp 37:191–202, 2016 . ©2015 Wiley Periodicals, Inc.